W poszukiwaniu adekwatnego podejscia do tzw. kategorii czasu (próba jezykowego kontrastu polsko- -wietnamskiego) - Tư, Lê Đình (Investigationes Linguisticae, 2010)
The contrastive analysis of Polish and Vietnamese literary works reveals many phenomena related to grammatical category of tense, which can not be explained using the concepts of traditional or non-traditional approaches to grammatical categories in general, and the category of tense in particular. These difficulties speak for the necessity of taking a more relevant approach to all language facts, which are labeled "tense". The purpose of our paper is to signal such an approach, which will serve as a theoretical basis for interlingual contrastive analysis. We claim that interlingual contrastive analysis of tense should not aim to find out the differences and/or similarities in the ways and/or the means expressing tenses, but, first of all, to elucidate the differences and/or similarities in the ways different languages look at the logical time, and the means used by them to define it.